GEOLOGICAL MODELLING OF LITHOSEQUENT BASED ON DEM AND FINITE ELEMENT METHOD INVERSION OF VES DATA - Bunga Elim Somba; Saiful Darman; Rachmat Zainuddin; Raihanda Dwimart Mangawe (AGROLAND The Agricultural Sciences Journal (e-Journal), 2022)
The aims of this study are to develop interpretation of structural geology in lithosequent using DEM and finite elemen method based on VES data. This research was conducted on June 2021 untill January 2022 at Pasang District, North Toraja. Four main point location were selected and recorded in google earth. Those points were processed using software QGIS for developing 3D model, Saga-GIS for interpolated DEM and VES for generating 1D and 2D geoelectrical modelling. Data were interpolated using Universal Kriging method and analysed using IP2WIN software. The results of these research shows that Geostatistical Universal Kriging can be used for interpolating DEM in lithosequent Pasang Village, by using as the variogram equation and yield 95,12% determinations; VES method in geoelectrical resistivity can be configure into 2D and produce clearer modeling of pseudo-section; The synthetics data can be generated from field measurement data and interpretation of 2D VES; Result of synthetic block on geoelectrical data can be inverted using Finite Element Method and generated clearer data; By using these methods, the thickness of weathering layer in lithosequent Pasang Village can be estimated and modelling.